A comparative study of the influence of N, N′-dialkyl vs. N, N′-diaryl-based electron donor ancillary ligands on photocurrent and photovoltage in dye-sensitized solar cells (DSSCs). Issue 31 (26th July 2017) - Ashraf, Saba; Yildirim, Erol; Akhtar, Javeed; Siddiqi, Humaira M.; El-Shafei, Ahmed
Abstract : In this study, we report the synthesis of a novel heteroleptic Ru(ii )-sensitizer, denoted asSD-1 ; moreover, its photophysical, electrochemical, and photovoltaic performances were compared with those ofN719 andK77-7 . Abstract : In this study, we report the synthesis of a novel heteroleptic Ru(ii )-sensitizer, (Ru(2, 2′-bipyridine-4, 4′-dicarboxylic acid)-4, 4′- bis (4-piperidin-1-yl)phenyl ethenyl)-(2, 2′-bipyridine) (NCS)2, denoted asSD-1 ; moreover, its photophysical, electrochemical, and photovoltaic performances were compared with those ofN719 andK77-7 ( N, N ′-diaryl Ru-sensitizer, namely Ru(2, 2′-bipyridine-4, 4′-dicarboxylic-acid)-4, 4′- bis (2-(4- N, N ′-diphenylaminophenyl)ethenyl)-2, 2′-bipyridine (NCS)2 ). The photovoltaic performance ofSD-1 outperformed those of N-719 andK77-7, particularly in the red region, and the overall efficiency ofSD-1 was 8.5% as compared to 8.0% ofK77-7 and 7.7% ofN719 under the same experimental device conditions. The superior light harvesting efficiency ofSD-1 can be attributed to the strong electron donor sp 3 -nitrogen, which is attached to two sp 3 -carbons (dialkyl), whereas in the case ofK77-7, all carbon atoms attached to the sp 3 -nitrogen are sp 2, which decrease the electron density on the latter and minimize the electron-donating power of the ancillary ligand inK77-7 . To gain a quantitative understanding of the electron density on nitrogen inSD-1 andK77-7, first-principle calculations using molecular and thermodynamic descriptors, such as frontier molecular orbitals, ground-state oxidation potential (GSOP), excited-state oxidation potential (ESOP), optical gap ( E 0–0 ), and charge distributions, were conducted in solution. In addition, for understanding the anchored structures of dyes on Ti24 O48, density functional theory (DFT) and time-dependent density functional theory (TD-DFT) were utilized. Results of computational studies are in excellent agreement with the experimental results, which can be used as a screening tool for the design of more efficient molecular motifs for DSSCs.